Effects of turbine height and cut-in speed on bat and swallow fatalities at wind energy facilities - Alexandra M. Anderson; Catherine B. Jardine; J.R. Zimmerling; Erin F. Baerwald; Christina M. Davy (FACETS, 2022)
Understanding the relationship between the height of wind turbines and wildlife fatalities is important for informing and mitigating wildlife collisions as ever taller and denser arrays of wind turbines are erected across the landscape. We examined relationships between turbine height and fatalities of bats and swallows at 811 turbines in Ontario, Canada, ranging from 119 to 186 m tall. We accounted for cut-in speeds, operational mitigation, and taller turbines projecting carcasses farther from the turbine base than shorter turbines. Fatalities of hoary bats (Lasiurus cinereus Palisot de Beauvois, 1796), silver-haired bats (Lasionycteris noctivagans Le Conte, 1831), and big brown bats (Eptesicus fuscus Palisot de Beauvois, 1796) increased with increased maximum blade height of turbines. In contrast, fatalities of little brown bat (Myotis lucifugus Le Conte, 1831) and eastern red bat (Lasiurus borealis Müller, 1776) decreased with increased turbine height. Fatalities of purple martins (Progne subis Linnaeus, 1758) and tree swallows (Tachycineta bicolor Vieillot, 1808) were higher at taller turbines than shorter turbines. However, fatalities of cliff swallow (Petrochelidon pyrrhonota Vieillot, 1817) and barn swallow (Hirundo rustica Linnaeus, 1758) were not associated with turbine height. Our results suggest that varying flight height among species may be one factor affecting collision risk.